Three axis machine to process small pieces - Garrudo, Paulo (2020)
This paper describes a machine designed to process small PVC pieces, used in automobile cable testing equipment. This machine should allow several different processing tasks without too much reconfiguration, thus providing a high level of automation. The solution is based on a three axis movable platform moving inside a cage structure where several tools are attached. This paper describes the machine control hardware and software, not the mechanical structure. The machine processes a piece at a time. The piece is placed in the platform and held in place by a gripper. The platform moves inside the cage placing the piece in the appropriate tool position, following a checklist of operations. The machine is controlled by a PC (Personal Computer), equipped with a commercial I/O interface board and a motion control board. The software developed is composed of three modules for the different control and configuration needs. One used after the machine is physically reconfigured. The second module allows the definition of the operations to be performed and respective coordinates. This module is used when a new series of pieces is to be processed. The third module controls the manufacturing process.